Reproduction of Warqa wa Gulshah Miniatures in a Basic Design Workshop - Sara Çebi (Art-Sanat)
This research examines a study where 10 first-year students from the Painting Department at Trabzon University’s Faculty of Fine Arts and Design collaborated during the 2023-2024 academic year to create 10 artworks as part of their basic art workshop course. The students were introduced to the story and history of the Warqa wa Gulshah epic written by Ayyukî in the 11th century, which is part of the Republic of Turkey Presidency of the National Palaces Administration Manuscript and Printed Works Collection, inventory number 841. They studied the miniatures alongside the narrative, then learned about artistic reproduction and reevaluated selected miniatures from the epic using basic art elements and Gestalt theory. Analyzing their reproduced works with contemporary integration and comparing chosen miniatures provided a robust platform for thorough examination and analysis of artworks. The study aimed to cultivate students’ interest in art history and enhance their skills in comprehensive artwork analysis. Beginning with analyzing the Warqa wa Gulshah miniatures, it proceeded to examine students’ works using basic art elements and Gestalt theory principles. Applications inspired by these miniatures helped students understand artwork structures and assess aesthetic merits, focusing on integrating visual elements into compositions.